Chonecoleaceae (Lophocoleineae) is a synonym of Cephaloziellaceae (Cephaloziineae) and Rivulariella (Jungermanniineae) belongs to Scapaniaceae s.l. (Cephaloziineae) - Patzak, Simon D. F.; Schäfer-Verwimp, Alfons; Váňa, Jiří; Renner, Matt A. M.; Peralta, Denilson F.; Heinrichs, Jochen (Phytotaxa, 2016)
Jungermannia doellingeri has alternatively been aligned with Harpanthaceae, Lophocoleaceae, Plagiochilaceae, and Lophoziaceae. Currently it is placed in a monogeneric family Chonecoleaceae of Jungermanniales suborder Lophocoleineae, as Chonecolea doellingeri. Maximum likelihood analyses of a chloroplast DNA rbcL-rps4 dataset of jungermannialean liverworts suggest a position of Chonecolea in Jungermanniales suborder Cephaloziineae and a synonymy of Chonecoleaceae and Cephaloziellaceae. The monospecific genus Rivulariella is not affiliated with Jungermanniaceae but related to Scapaniaceae s.l. (including Anastrophyllaceae and Lophoziaceae).